Keeping Concrete from Catching Cold - Dow Chemical Company (1939)
Advertisement for Dowflake Calcium Chloride, a product of the Dow Chemical Company marketed for use as a curing agent to help facilitate water absorption during the preparation of concrete. The advertisement features workers pouring concrete in inclement weather conditions, underscoring Dowflake's ability to reduce freezing hazards and speed up construction time, particularly in cooler temperatures.
Keywords: Concrete; Chemical industry; Dow Chemical Company; Concrete construction; Corporations; Advertising; Calcium chloride